Dissipation effects in superconducting heterostructures with tungsten nanorods as weak links - Shaternik, V.E.; Shapovalov, A.P.; Suvorov, O.Yu.; Zhitlukhina, E.S.; Belogolovskii, M.A.; Febvre, P.; Kordyuk, A.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2018)
Thin-film hybrid heterostructures formed by superconducting molybdenum-rhenium-alloy films with a critical temperature of about 9 K and nanoscale silicon-based semiconducting interlayers with metallic tungsten nanorods have been fabricated and studied. Current-voltage characteristics of the junctions were measured at 4.2 K and under influence of 11 GHz microwave irradiation. The evidence of a quasi-one-dimensional transport through the tungsten weak links disrupted by phase-slip centers was revealed in MoRe/doped Si/MoRe trilayers under irradiation by a high-frequency field. Also, measured current-voltage characteristics of five-layer MoRe/doped Si/MoRe/doped Si/MoRe devices exhibit a strong influence of a dissipation state in the MoRe interlayer. Namely, the switching from a superconducting state with low dissipation to a finite-conductance regime can be initiated by the emergence of an extra phase-slip center in the MoRe interlayer. Possible physical mechanisms of the two findings are discussed.